Iris and periocular biometric recognition - Rathgeb, Christian; Busch, Christoph (IET security series ;, 2017)
The book reviews developments in the following fields: periocular biometrics; robust iris image segmentation; iris image quality metrics; iris biometric indexing; biometric recognition; best periocular region identification; presentation attack resistant robust biometric ocular system; soft biometric classification; gender classification; near infrared iris images; age predictive biometrics; contact lens detection; software attacks; privacy protection; forensics; iris biometric template protection; privacy-preserving distance computation; IrisCodes; iris sensor identification; iris image matching; embedded systems; and mobile iris recognition.